The role of social dialogue (civil society participation) in policy decision-making in South Africa: the case study of NEDLAC - Ngxabi, Siziphiwe (My University, 2016)
South Africa enshrines itself as a democratic developing country that adheres to the principles of good governance and acknowledges the role that civil society participation in state affairs can have. The purpose of this study was to establish the role and effectiveness of NEDLAC’s social dialogue process through evaluating the contribution of civil society participation in the Development Chamber; and to understand the relationship between NEDLAC’s social dialogue model and the World Bank ideology on civil society participation in policy making. The study highlights that NEDLAC remains one of the key vehicles for social dialogue in South Africa and there have been positive contributions by civil society participation in the NEDLAC process. It takes its premise from the ILO model of social dialogue, whilst it also adapts from the World Bank ideology of civil society participation by including civil society in the process, through the Development Chamber. However, the effectiveness of civil society participation in policy making through NEDLAC is at risk due to the impact of the changing socioeconomic environment. In many ways this study highlights contradictions in South Africa’s social dialogue process. The Development Chamber is not being optimally used for its intended purposes as representativity and accountability of the community organisations are a concern; whilst there is an increasingly active civil society, demonstrated by civil unrest, which is not part of this social dialogue process.
Submitted in partial fulfilment of the degree: Masters in Development Theory and Policy in the Faculty of Commerce, Law and Management at the University of Witwatersrand
Keywords: Civil society; Participation; Social dialogue; Good governance; Policy making; NEDLAC